Evaluation of SUV roof crush analysis using alternative non-linear structural analysis solver - Tofrowaih, Khairul Amri; Sulaiman, Saiful Naim; Azlan, Khairul Azri; Ab Razak, Mohd Suffian; Abdul Rahman, Mohd Hafizi; Lubis, Abdul Munir Hidayat Syah; M.S.Abdul Samad; A. L.Achmad Joehary (Society of Automotive Engineers Malaysia, 2021)
Accidents involving rollover in countries although low in numbers, recorded the highest Killed & Severed Injury (KSI) index and highest fatality index. The roof Crush Resistance test has been found to be one of the relevant tests to anticipate the impact of rollover incidents. However, a very limited number of research has been done on roof crush analysis using non-linear RADIOSS solver. Therefore, the aim of this study is to develop an FE model for roof crush analysis using RADIOSS and to validate and compare the RADIOSS model to LS-DYNA. An SUV is selected, and its finite element (FE) model obtained from CCSA is converted from LS-DYNA to RADIOSS with equivalent element type, element properties, material, and damage modelling adjustment. The analysis is performed according to FMVSS 216 standard and the result of deformation and SWR plot is compared to the NHTSA report. From the result, it has been shown that RADIOSS is a good alternative to run highly non-linear analysis such as roof crush analysis.